The Impact of Using the Intermediate Language on Teaching Arabic to Non-Arabic Speakers/ أثر استخدام اللغة الوسيطة في تعليم اللغة العربية للناطقين بغيرها - Asmaa Mohamed Rady (Universitas Negeri Malang, 2021)
The main objective of teaching any foreign language is to enable the learner to employ the four language skills (reading, writing, listening, and speaking); In order to develop these skills, the teacher must choose the appropriate teaching methods and employ them during the educational process. This study aims to examine one of the most important strategies and issues directly related to teaching Arabic as a foreign language. The most controversial between specialists and professionals in this field is the Intermediate language and the effectiveness of using this language in teaching Arabic to non-native speakers in language skills: speaking, listening, and reading, and writing. Between supporters and opponents, this issue remained the subject of controversy and endless discussion about its use or lack of assistance. In this study, the descriptive qualitative approach was applied. The study population consists of bachelor students of non-native speakers of the Arabic language at the State University of Malang. Their number is (15) learners in the first and second levels in the academic year 2020/2021. The study reached the following results: There is no effect of the intermediate language on teaching reading and writing skills for the first and second levels, while there is an effect of the intermediate language on the skills of listening and speaking for the second level.